2016
DOI: 10.1111/and.12570
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serum vitamin D levels in Chinese infertile men

Abstract: Recently, the question of whether vitamin D exerts an effect on the pathogenic process of infertility has become the centre of attention. There are some controversial conclusions on this issue. Based on previous studies, we sought to explore the difference of serum 25-hydroxyvitamin D , 1,25-dihydroxyvitamin D levels between infertile patients and fertile men, and to find the influence on semen quality. The analysis of serum 25-hydroxyvitamin D level showed no significant difference between infertile patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
0
41
0
1
Order By: Relevance
“…Prolactin receptors have been found in Leydig and Sertoli cells in male testes, and high serum PRL levels reduce spermatogenesis, sperm motility and quality by reducing the pulsatile release of FSH, LH and testosterone (Blomberg et al, ; Boisen et al, ; Zhu et al, ). In our study, serum PRL levels were significantly elevated in the infertile groups than in the fertile group.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Prolactin receptors have been found in Leydig and Sertoli cells in male testes, and high serum PRL levels reduce spermatogenesis, sperm motility and quality by reducing the pulsatile release of FSH, LH and testosterone (Blomberg et al, ; Boisen et al, ; Zhu et al, ). In our study, serum PRL levels were significantly elevated in the infertile groups than in the fertile group.…”
Section: Discussionmentioning
confidence: 90%
“…Follicle‐stimulating hormone and luteinising hormone are essential for normal spermatogenesis in men. It has been shown that serum FSH and LH levels increase in cases of spermatogenesis slowing down, decreased TPMSC and azoospermia (Chen, Hsieh, Yu, & Chang, ; Inal, Kahyaoglu, Turkkani, Tuzluoglu, & Yilmaz, ; Zhu et al, ). In our study, in line with previous studies, serum FSH and LH levels were significantly higher in men with oligospermia and azoospermia than in fertile men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations